The Cinema of Naruse Mikio : Women and Japanese Modernity - Russell, Catherine, 1959- (Book collections on Project MUSE., 2008)
The first English-language book dedicated to an analysis of Naruse Mikio, one of Japan's most prolific directors, whose films provide unique insight into the representation of female subjectivity and modernity in Japan.